Assessment of Metals and Metalloids Accumulation in Wastewater Irrigated Soil and Uptake by Pumpkin (Cucurbita maxima) at Sargodha, Pakistan - Iqbal Khan, Zafar; Bibi, Zahara; Ahmad, Kafeel; Ashraf, Muhammad; Aisha Akram, Nudrat; Arshad, Fahim (Asian Journal of Chemistry, 2013)
This research was conducted to evaluate the metal and metalloid concentrations in soil and Cucurbita maxima. A composite of soil and vegetable samples were collected from two sites of district Sargodha, Pakistan receiving domestic sewage water. Soil and vegetable samples were digested and analyzed for metal contents. The levels of six different metals and metalloids in soil viz., Co, Ni, Cu, As, Zn and Se were found to be 19.61, 3.29, 11.97, 26.40, 3.84 and 2.36 mg kg-1 at site-I and 19.63, 3.57, 11.76, 26.39, 3.73 and 2.29 mg kg-1 at site-II, respectively. The metal contamination levels at both sites were almost similar. The study showed that constant supply of raw water for irrigation resulted in accumulation of metals and metalloids in the vegetable above the maximum permissible limit. The mean concentrations of metals and metalloids in edible portion of Cucurbita maxima in mg kg-1 at site-I were 0.544 for Co, 4.33 for Ni, 23.43 for Cu, 11.72 for As, 61.77 for Zn and 0.835 for Se and at site-II 0.760 for Co, 4.827 for Ni, 23.49 for Cu, 9.097 for As, 58.65 for Zn and 0.833 for Se. The transfer factor indicated that Zn had the strongest capacity of metal accumulation from the soil to the vegetable at both sites. Pollution load index for Se, Cu and Co was greater than 1 at both sites. Health risk index due to intake of Cucurbita maxima (mg day-1) was 0.07 for Co, 1.24 for Ni, 3.37 for Cu, 224.63 for As, 1.18 for Zn, 0.90 for Se at site-I and 0.101 for Co, 1.38 for Ni, 3.37 for Cu, 174.35 for As, 1.12 for Zn and 0.95 for Se at site-II. Concerning the consumption routine of residents in sampling area, the daily intake of As, Cu, Ni and Zn was beyond the oral dose, thus eating of Cucurbita maxima is not considered to be safe for inhabitants of the sampling sites.